La traduzione pedagogica: una risorsa motivazionale nell’insegnamento della LS/L2 - D'Amico, Tiziana (Paidia i Literatura, 2021)
The work focuses on pedagogical translation as motivational tool. In particular, as a tool that works on the motivation of the beginner L2 student. The specific working language is Czech, but we believe that what has been observed may also apply to other languages, whose teaching is characterized by a small number of students. The aim is to offer a theoretical and practical framework to better frame translation as a teaching tool even for beginners L2 at the University. After presenting what we mean with lower-frequency language, pedagogical translation and beginner group, we move into the work with translation and how this activity fits into the investigation of motivations in the LS.